Evaluación del comportamiento mecánico de uniones de guadua angustifolia kunth (GAK)-polietileno de baja densidad (PEBD) (2020)
This work, describing the construction and mechanical evaluation of Guadua-Polymer joints, in the construction of structures (50-80 kg), for this purpose, the most common types of joints were initially defined in a basic furniture structure. The selected joints: Straight Join, Right Angle Join (90o), and Y-Join (120o), were built to apply the loading system to them, taking weight, diameter and bending data. In addition to this, cross-sections of the joints were performed, to evaluate the morphology of the joints. After the analysis of the data it was found that the combination of Guadua-Polymer materials in a bond, are a real alternative in the construction and design of new basic furniture elements.